2016
DOI: 10.1002/2015wr018428
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the full potential of Earth observation during the 2015 Texas flood disaster

Abstract: Intense rainfall during late April and early May 2015 in Texas and Oklahoma led to widespread and sustained flooding in several river basins. Texas state agencies relevant to emergency response were activated when severe weather then ensued for 6 weeks from 8 May until 19 June following Tropical Storm Bill. An international team of scientists and flood response experts assembled and collaborated with decision-making authorities for user-driven high-resolution satellite acquisitions over the most critical areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 8 publications
0
18
0
1
Order By: Relevance
“…Satellite‐based early flood warning systems likely have the greatest utility for cities that are located far downstream from basin headwaters and do not have well‐developed gauge networks in place. This being said, we note that low‐latency remote sensing observations can still greatly benefit cities located in relatively small basins with well‐developed infrastructure (e.g., Schumann et al, ). Similar to cities, areas containing fewer dams or dams with larger contributing areas will potentially benefit the most from NRT satellite products, at least when considering data latency alone.…”
Section: Discussionmentioning
confidence: 95%
“…Satellite‐based early flood warning systems likely have the greatest utility for cities that are located far downstream from basin headwaters and do not have well‐developed gauge networks in place. This being said, we note that low‐latency remote sensing observations can still greatly benefit cities located in relatively small basins with well‐developed infrastructure (e.g., Schumann et al, ). Similar to cities, areas containing fewer dams or dams with larger contributing areas will potentially benefit the most from NRT satellite products, at least when considering data latency alone.…”
Section: Discussionmentioning
confidence: 95%
“…This situation is, of course, frustrating to both the decision maker and the product developer, whose flood maps may not be used as intended or indeed may not be used at all. Schumann et al () outlined several reasons for this apparent underutilization by decision makers: (a) limited time and capacity to understand, process, and handle the datasets; (b) limited near real‐time data accessibility, bandwidth, and sharing capacity; (c) incompatibility between user platforms and geospatial data formats; (d) data availability may be simply unknown and/or data latency (lag from acquisition to delivery) may be inadequate; and (e) limited understanding by scientists and engineers about end‐user product and timing needs.…”
Section: The Need For More Scientific Rigour and Accountability In Flmentioning
confidence: 99%
“…However, it is this contemporary push towards big and novel concepts that may be partly responsible for the notable lack of rigorous local let‐alone global‐scale validation (i.e., accuracy assessment) of satellite products. Consequently, scientific accountability is missing, particularly in the case of satellite flood maps that need to be delivered in a timely manner and often under conditions of very limited resources during disasters to assist response operations in any location (as outlined by Schumann, Frye, et al, , in a detailed account of the Texas 2015 flood disaster).…”
Section: The Need For More Scientific Rigour and Accountability In Flmentioning
confidence: 99%
“…Compared with high spatial resolution sensors, such as optical sensors like the Landsat and radar sensors, which usually offer a 6-16 day repeat cycle, operational satellites usually have relatively high temporal resolution, of twice per day for polar orbiting satellites and 5-30 min for operational geostationary satellites. As a flood is usually a short term event, operational satellites with large area coverage and frequent revisit, either used alone or in combination with other high spatial resolution sensors, or complemented by numerical model simulations, have played significant roles in the detection and monitoring of large floods [18][19][20][21]. For example, Schumann et al [18] demonstrated an application for the May-June 2015 Texas flood disaster using only satellite observations.…”
Section: Introductionmentioning
confidence: 99%
“…As a flood is usually a short term event, operational satellites with large area coverage and frequent revisit, either used alone or in combination with other high spatial resolution sensors, or complemented by numerical model simulations, have played significant roles in the detection and monitoring of large floods [18][19][20][21]. For example, Schumann et al [18] demonstrated an application for the May-June 2015 Texas flood disaster using only satellite observations. In that case, MODIS flood maps at a 250 m resolution were composited with many images from other high resolution sensors like the Landsat 7/8 at 30 m resolution and Sentinel-1 at various resolution, and so on.…”
Section: Introductionmentioning
confidence: 99%